The Impact of Social Media Exposure and Peer Group Towards Gen Z Decision To Visit Pasar Kangen Yogyakarta - Amali, Muhammad Thoyib; Pudrianisa, Sheila Lestari Giza (Fakultas Ilmu Komunikasi UKWMS, 2024)
The Special Region of Yogyakarta has taken proactive measures to boost tourist numbers after COVID-19 by reinstating various cultural events. Pasar Kangen is a recurring annual event that garners substantial visitor interest. Looking at the long journey of Pasar Kangen that has been held since 2007, this agenda has now become a destination for various groups of tourists, including Gen Z. This research aims to analyze the influence of social media exposure and peer group on Gen Z decision to visit Pasar Kangen Yogyakarta. This research utilized a quantitative approach, involving a survey conducted among 100 Gen Z tourists who visited Pasar Kangen in 2023. The data analysis technique used to test the hypothesis in this research was multiple regression using SmartPLS program. The research results show that social media exposure and peer group have a positive and significant effect on Gen Z decision to visit Pasar Kangen. Furthermore, as a managerial implication, the event organizer of Pasar Kangen can expand their reach of social media exposure through collaboration with digital key opinion leaders, especially those who are mostly followed by Gen Z on social media.